Malawi s organic market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Midlands Organic Growers Association (MOGA) of Malawi has established a market in the capital Lilongwe selling directly to consumers, with support from the German agency GTZ. The market is astutely located in a low-density residential area, a...